Clinico-mycological profile of tinea capitis and its comparative response to griseofulvin versus terbinafine - Ali Mikaeili; Hossein Kavoussi; Amir Hosein Hashemian; Mahdokht Shabandoost Gheshtemi; Reza Kavoussi (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Tinea capitis is the most common superficial mycosis in children. This disease is a contagious infection with worldwide distribution and is occasionally associated with permanent alopecia. The treatment of this infection usually requires the administration of appropriate oral antifungal agents. The current study was conducted to evaluate the clinico-mycological profile of tinea capitis and compare the efficiency of oral griseofulvin and terbinafine in the treatment of this disease. Materials and Methods: This study was conducted on 69 patients, including 23 females (33.3%) and 46 males (66.7%), clinically suspected of tinea capitis. After the confirmation of tinea capitis diagnosis through direct examination, the subjects were randomly assigned into two groups of griseofulvin and terbinafine. Demographic data, clinical and mycological characteristics, and therapeutic outcome were recorded for both groups. Results: According to the results, tinea capitis was more common in children younger than 15 years (73.9%), athletes (37.7%), and males (66.7%), and those with frontal involvement (34.8%), non-inflammatory type (68.1%), endothrix (69.6%), and Trichophyton tonsurans species (41.7%). The griseofulvin and terbinafine groups had the treatment success rates of 90.9% and 80.6%, respectively (P=0.311). The griseofulvin group had a shorter therapeutic course than the terbinafine group (P=0.129). Conclusion: Although our findings demonstrated that both griseofulvin and terbinafine were effective in the treatment of tinea capitis, griseofulvin showed a little higher efficacy in this regard. Consideration of some variables, such as age, associated risk factors, clinical type, hair involvement pattern, and dominant pathogenic species, is important in the determination of the drugs.